La oxidación lipídica en la cadena de producción acuícola - Landines Parra, Miguel Ángel; Zambrano Navarrete, Jorge Andrés (Revista de Investigación Agraria y Ambiental, 2019)
Aquaculture industry has sustained its development on the use of products obtained from marine fish species. Main industrial products in this field are both the flour and fish oil, which have a high nutritional and economic value. Fish oil has been found to be a scarce raw material, which has a high content of polyunsaturated fatty acids (PUFA n-3) and has been classified as a functional food because of the benefits they bring on the consumer’s health. Paradoxically, high PUFA n-3 content makes the fish oil highly susceptible to the autooxidation processes that lead to the transformation of PUFA N-3 in peroxides, aldehydes, ketones and polymers that are responsible for oxidative cell damage. In this document we explore the processes in which primary and secondary products are generated through oxidation, and the protection mechanisms against oxidative damage and the negative effect of primary and secondary products of lipid autoxidation on nutritional quality of balanced feeds, fish health and quality of meat products for human consumption. En el campo alimenticio, la industria acuícola ha sustentado su desarrollo en la utilización de materias primas provenientes de la cadena de procesamiento especies de peces de origen marino. Los principales productos industriales de esta cadena son la harina y el aceite de pescado, los cuales tienen un alto valor nutricional y económico. En el caso particular del aceite de pescado, se ha encontrado que es una materia prima escasa, que presenta un alto contenido de ácidos grasos poliinsaturados (AGPI omega 3) y que ha sido catalogada como alimento funcional por los beneficios para la salud del consumidor. Paradójicamente el alto contenido de AGPI n-3 hace del aceite de pescado una materia prima altamente susceptible a los procesos de auto oxidación que promueven la transformación de los ácidos grasos en Peróxidos, aldehídos, cetonas y polímeros, responsables del daño celular oxidativo. En el presente documento describimos los procesos de generación de productos primarios y ...